Influence of Three Probiotics Strains, Lactobacillus rhamnosus GG, Bifidobacterium animalis subsp. Lactis BB-12 and Saccharomyces boulardii CNCM I-745 on the Biochemical and Haematological Profiles and Body Weight of Healthy Rabbits - Louiza Kadja; Amira Leila Dib; Nedjoua Lakhdara; Assia Bouaziz; Elena Espigares; Mohammed Gagaoua (Biology, 2021)
This study aimed to investigate the effects of three strains of probiotics, these being Lactobacillus rhamnosus GG, Bifidobacterium animalis subsp. Lactis BB-12 and Saccharomyces boulardii CNCM I-745, on the body weight, animal performances and blood parameters of rabbits (male and female) of the ITELV2006 strain. The supplementation of the feed of the rabbits with the three probiotic strains allowed observing positive effects on most of the biochemical and haematological parameters investigated during a period of 60 days (30 days of supplementation and 30 days without treatment). Further, there was a significant improvement in the body weight of the rabbits at the end of the experiment. The effect of the three probiotics investigated in this trial was found to be related to the sex of the rabbits and to the intake period (duration). Ultimately, these findings raise the possibility of using probiotics to investigate in an in-depth and specific manner based on fixed factors such as the strain, the gender and age of the animals, the main underlying mechanisms and effects, which would allow achieving optimal and adapted health benefits and sustainable production. In the context of animal production, it is worth investigating in a targeted study the effect of the three strains on muscle growth and development and finding evidence of the possible consequences on meat quality traits of the rabbits supplemented with probiotics.